Isolation and Screening of Rhizobacteria and Their Potential as Plant Growth Promoters and Biological Control Agents for Bacterial Wilt of Tomato - Hesti Susilo, Bambang (2004)
Isolation of rhizobacteria was carried out from rhizosphere of tomato, eggplant, and groundnut. One hundred and eighty five isolates were obtained and screened for antagonism against Ralstonia solanacearum. Out of these, 37 showed antagonistic activity. Five out of the 37 antagonists, namely Pseudomonas aeruginosa (Pa I and Pa II), Pseudomonas sp. (FA4) and Serratia marcescens (Sm R and Sm E), were then chosen for further studies. Tomato seeds were bio-primed with the five antagonists and seed germination was assessed. Bio-priming of tomato seeds with the antagonist either individually or in combination had no significant effect on seed germination when compared to either the methylcellulose or distilled water control. Thus, the bio-priming did not give any detrimental effect on seed germination. The use of methylcellulose as binder was also not phytotoxic. The antagonists were tested for the ability to produce IAA and solubilize phosphate in vitro. All antagonists produced IAA at varying concentrations, while only Pa I, Pa II and FA4 were phosphate solubilizers. Evaluation of Pa II, Pa I and Sm E to enhance tomato plant growth was carried out in two greenhouse trials. Firstly, Pa II and Sm E were evaluated based on their production of IAA. Secondly, Pa II and Pa I were evaluated based on their ability to solubilize phosphate. Results from the first trial showed that treatment with Pa II gave significantly (P ≤ 0.01) higher fresh and dry weight, plant height and root length compared to plants treated with Sm E and the control indicating that the increased growth could possibly be due to the IAA production. In the second trial, the individual treatments with Pa II and Pa I, in a P-deficient soil amended with rock phosphate, gave significantly (P ≤ 0.01) higher fresh and dry weight, and plant height compared to the control. Results from the second trial indicated that the ability of the isolates to solubilize phosphate could be another mechanism involved in the growth promotion. Tomato seeds bio-primed with the five antagonists, individually and in combination, followed by application of the antagonists incorporated into rhizosphere using pottingmixture were evaluated for their efficacy in controlling bacterial wilt under greenhouse condition. All treatments significantly (P ≤ 0.01) reduced severity of the disease and the disease incidence when compared to the control. The disease incidence was reduced by 83.33% with individual treatments of Sm E, Pa I and Pa II. Combinations of Pa I + Pa II and Sm E + Sm R were able to reduce the disease incidence by 66.67 and 50% respectively, while individual treatment of FA4 and Sm R gave the reduction of 75 and 41.67% respectively. In conclusion, the five antagonists have the potential as plant growth-promoters and as biological control agents for bacterial wilt of tomato.